(untitled) (Mantichora. Italian Journal of Performance Studies, 2025)
The essay aims to produce a reading of La Cupa by Mimmo Borrelli (2018). An attempt will be offered to highlight the processes that led to the creation of the work, indebted towards an oral heritage made up of interviews, proverbs and real events; furthermore, an analysis of some of characters will be conducted: they represent the sins that afflict the tuff quarry in which the story is set, that becomes a metaphor for a world that has lost its values. The theatre, according to Borrelli, in the face of this ferocious reality, has the duty to move the souls of spectators to raise awareness of the humanity’s unworthiness.